The Effectiveness Of Pregnancy Gymnastics On The Relaxation Of Pregnant Women In Disaster-Affected Areas - Helpi Nelwatri; Erianjoni Erianjoni; Yunita Safitri (STAMINA, 2026)
Pregnant women are a vulnerable group to psychological stress, especially those living in disaster-affected areas. Prolonged exposure to stress during pregnancy can negatively impact maternal and fetal health. Pregnancy exercise as a form of non-pharmacological prenatal exercise has the potential to increase relaxation and reduce anxiety in pregnant women, but empirical evidence in the context of disaster-affected areas is still limited, especially in Padang City. This study aims to analyze the effectiveness of pregnancy exercise on increasing relaxation in pregnant women in disaster-affected areas in Padang City. This study used a quasi-experimental design with a pretest-posttest control group approach. The sample consisted of 20 pregnant women in their second–third trimesters who lived in disaster-affected areas in Padang City, who were divided into an intervention group (n=10) and a control group (n=10). The intervention group was given structured pregnancy exercise for 8 weeks with a frequency of three times per week, while the control group received standard antenatal care. The level of relaxation was measured using the relaxation scale of pregnant women before and after the intervention. Data analysis was performed using paired t-test, independent t-test, and linear regression with a significance level of 0.05. The results showed a significant increase in relaxation scores in the intervention group after participating in prenatal exercise (mean difference = 24.4; p < 0.001), while the control group did not show a significant change (p = 0.087). Post-intervention relaxation scores in the intervention group were significantly higher than those in the control group (p < 0.001), with a very large effect size (Cohen's d = 1.92). Multivariate analysis showed that prenatal exercise was the dominant predictor of increased relaxation in pregnant women (β = 0.61; p < 0.001), after controlling for age, parity, and trimester of pregnancy. Prenatal exercise was shown to be effective at increasing relaxation among pregnant women in disaster-affected areas of Padang City. This intervention can be recommended as part of promotive and preventive antenatal care, especially in disaster-prone areas, to support the psychological well-being of pregnant women